2021
DOI: 10.1002/prm2.12034
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for mortality in patients with congenital duodenal obstruction at DR. Moewardi Hospital Surakarta

Abstract: Background: Congenital duodenal obstruction is the most common congenital abnormalities in newborn. Almost 50% of all cases of congential abnormalities is duodenal obstruction. Several conditions of congenital obstruction can worsen a patient's prognosis, such as prematurity, low birth weight (LBW), other congenital abnormalities, type of obstruction, and the type of surgery performed. Objective: To identify prognostic factors for mortality in patients with congenital duodenal obstruction in Dr. Moewardi Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Estiarla found that 60% of the samples were of the total obstruction type, and as many as 55% of patients with duodenal obstruction died. 15 Brantberg et al conducted a study with 29 newborns with duodenal obstruction, in which 18 (62%) died (prenatal or postnatal) or had substantial developmental impairments. A total of 10 of the 21 children alive (48%) had substantial developmental disabilities.…”
Section: Apghnmentioning
confidence: 99%
“…Estiarla found that 60% of the samples were of the total obstruction type, and as many as 55% of patients with duodenal obstruction died. 15 Brantberg et al conducted a study with 29 newborns with duodenal obstruction, in which 18 (62%) died (prenatal or postnatal) or had substantial developmental impairments. A total of 10 of the 21 children alive (48%) had substantial developmental disabilities.…”
Section: Apghnmentioning
confidence: 99%
“…Risk factors linked to mortality encompass complex cardiac abnormalities, preterm birth, sepsis, pneumonia, and surgical complications like short bowel syndrome, leaky anastomosis, and gastroduodenal dysfunction. Notably, almost 80% of mortality cases are attributed to multiple congenital abnormalities and sepsis [7]. Mortality frequently results from delayed treatment and postoperative complications.…”
Section: Introductionmentioning
confidence: 99%